ANALISIS PERBANDINGAN NILAI IRI BERDASARKAN VARIASI RENTANG PEMBACAAN NAASRA - Siahaan, Doan Arinata; Surbakti, Medis Sejahtera (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Pavement will cause tensions continuously due to traffic loads which may result in damage to the pavement. For this case, the detection and repairation of damage early on pavement will prevent damage which may be developed into a pavement failure. Survey of  the condition of the road is one of the early efforts made ​​, in this case drive comfort is the most important part of the driver in assessing the road conditions which are influenced by the level of the ruggedness of  road surface . To find out the level of flatness of the road, which is now developed method is the measurement of flatness roads using NAASRA methods with general settings on halda as 100 m , but with this setting, we can  still found  highly enough  in ruggedness which  has caused many feeling uncomfortable while driving. This is what underlies  research of ruggedness or commonly known as IRI by comparing it with halda 50m and 200m in  the general Settings. This study uses the International Roughness Index (IRI) in determining the level of discomfort regarding road driving stability. IRI value is​​ obtained from direct field observations using roughometer-NAASRA. Based on the analysis result, getting a better result such as  relatively small IRI value, therefore the settings halda 50 would be better  used. But with a better  rate  the sensitivity of  the road  handling is likely reduced. This is in contrast with the halda settings 100 which will produce values ​​that tend to be large, but with the result, the priority levels of  handling will be better.